2021
DOI: 10.1111/ijlh.13586
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic relevance of long noncoding RNAs CRNDE and AOX2P in adult acute myeloid leukemia

Abstract: Introduction Several long noncoding RNAs (lncRNAs) have been demonstrated to play a critical role in the tumorigenesis of acute myeloid leukemia (AML), and altered expression of certain lncRNAs has been recognized as a potential prognostic marker in AML patients. Here, we sought to determine whether the expression of the lncRNA colorectal neoplasia differentially expressed (CRNDE) and aldehyde oxidase 2 pseudogene (AOX2P) is associated with clinicopathological features and clinical outcome of patients with AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Especially, Colorectal neoplasia differentially expressed (CRNDE) is a well-known long non-coding RNA which was considered to play crucial roles in the development of multiple cancers [ 35 ]. Moreover, it was highly expressed in AML [ 35 , 36 ], displayed functional roles in AML proliferation [ 37 ] and indicated by previous analyses to have prognostic value in AML [ 36 , 38 ]. Explorations focusing on the detailed mechanisms of CRNDE in P-AML pathology might help to identify a promising therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, Colorectal neoplasia differentially expressed (CRNDE) is a well-known long non-coding RNA which was considered to play crucial roles in the development of multiple cancers [ 35 ]. Moreover, it was highly expressed in AML [ 35 , 36 ], displayed functional roles in AML proliferation [ 37 ] and indicated by previous analyses to have prognostic value in AML [ 36 , 38 ]. Explorations focusing on the detailed mechanisms of CRNDE in P-AML pathology might help to identify a promising therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In AML CRNDE has an oncogenic function. High expression of CRNDE is associated with lower CR and shorter disease-free survival (DFS) and over-all survival (OS), and therefore can be used as a molecular marker predicting inferior outcome [103,104]. Especially high expression level was detected among APL and NPM1-mutated AML patients, promoting proliferation of leukemic cells and blocking myeloid differentiation.…”
Section: Lncrna Crndementioning
confidence: 99%
“…However, the precise functional roles of CRNDE in NPM1 mutated AML remains unclear. Recently, Hola et al conducted qRT-PCR based expression analysis of CRNDE from the diagnostic blood samples of 200 de novo adult AML patients compared to 50 healthy control samples, which revealed that upregulation of CRNDE was an adverse independent prognostic marker for complete remission in CN-AML patients [29].…”
Section: Long Noncoding Rna Overexpressed In Npm1-mutated Acute Myelo...mentioning
confidence: 99%